ESG Disclosure and Market Capitalization: The Mediating Role of Firm Performance - Vina Alviana; Dewi Sriani; Niluh Putu Dian Rosalina Handayani Narsa (Journal of Trends Economics and Accounting Research, 2025)
This research aims to investigate the effect ESG Disclosure on market capitalization with firm performance as a mediating variable. The population in this study are LQ45 companies indexed in Indonesian Stock Exchange (IDX) in the period of 2017-2022 with 113 firm year observation as a final sample. The results show that ESG Disclosure has a negative effect on market capitalization, meanwhile ESG disclosure has no effect on firm performance. Firm performance has no effect on market capitalization. Therefore, firm performance can’t mediate the relationship between ESG disclosure and market capitalization. The novelty of this study is using firm performance as intervening variable. The results provide practical insight to companies, investors and policy makers regarding the effect of ESG disclosure on market capitalization.